2021
DOI: 10.1002/jsfa.11102
|View full text |Cite
|
Sign up to set email alerts
|

Water productivity, yield and agronomic attributes of maize crop in response to varied irrigation levels and biochar–compost application

Abstract: BACKGROUND Due to the rapid increase in world population, the demand for freshwater is increasing day by day. There is also immense pressure on the agriculture sector to produce more food with limited supplies of water. About 75% of freshwater is used in crop production out of which 63% is lost due to poor farm practices and evapotranspiration. Enhancement of crop water productivity for sustainable agriculture production especially in areas having water scarcity plausibly contributes towards the solution of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Results showed that the use of a mixture of PG and BC improved the soil's hydrophysical and chemical properties, resulting in less evapotranspiration losses, making water available for crops for a longer period which protecting the crop against water stress and consequently, increasing WUE and WP. Our results concur with (Faloye et al, 2020, Bossolani et al, 2021 andZahra et al, 2021). Studies show that BC has a high porosity and surface area which leading to an increase in the general soil porosity and water content, reducing water stress for plants (Batista et al, 2018).…”
Section: -Impact Of Water Stress Applications Bc Pg Either Alone or I...supporting
confidence: 91%
“…Results showed that the use of a mixture of PG and BC improved the soil's hydrophysical and chemical properties, resulting in less evapotranspiration losses, making water available for crops for a longer period which protecting the crop against water stress and consequently, increasing WUE and WP. Our results concur with (Faloye et al, 2020, Bossolani et al, 2021 andZahra et al, 2021). Studies show that BC has a high porosity and surface area which leading to an increase in the general soil porosity and water content, reducing water stress for plants (Batista et al, 2018).…”
Section: -Impact Of Water Stress Applications Bc Pg Either Alone or I...supporting
confidence: 91%
“…Furthermore, organic amendments provide labile carbon sources that stimulate microbial growth and activity, leading to enhanced nutrient cycling and plant growth. Organic amendments have been demonstrated to have positive effects on maize grain yield when applied independently (114) or in combination with biochar (115).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the increase in SOM was mainly attributed to the high organic carbon content of poorly pyrolyzed biochar ( Table 2 ). Moreover, biochar has positive priming effects on soil microbial activity and root growth ( Danso et al., 2019 ; Zahra et al., 2021 ), both of which may regulate SOM turnover, since more microbial activity could accelerate SOM mineralization. The SOM under the W15 regime was higher than that under the W35 regime for the same biochar amendment, which showed that a greater amount of irrigation and soil moisture were more beneficial to the formation of SOM for these two studied years.…”
Section: Discussionmentioning
confidence: 99%